The effect of eight weeks of spirulina supplementation and resistance and interval aerobic training on skeletal muscle CXCL1 gene expression and liver enzymes in male rats - Mohammad javad Jalali; Rozita Fathi; Khadijeh Nasiri; Abolfazl Akbari (Shahid Beheshti University, 2023)
Background and Purpose: Inactivity and on the other hand physical exercise are known as factors related to indicators of liver damage. However, the role of many types of interval, including interval and resistance training, and the consumption of certain dietary supplements, including spirulina, on immune and inflammatory factors is not fully understood. Therefore, the aim of this research was to determine the effect of eight weeks of spirulina supplementation and resistance and intermittent aerobic training on liver tissue activity and CXCL1 gene expression in muscle tissue of Males rats.Materials and Methods: In this semi-experimental research, 65-weeks-old male Wistar rats with an average weight of 246.4 ± 24.6g were randomly assigned to six groups: interval training + spirulina supplement, resistance training + spirulina supplement, control + spirulina supplement, interval training + saline, resistance training + saline, control + saline. Based on this, the amount of spirulina supplement in the spirulina supplement consumption groups was 500 mg/kg body weight. The interval training group performed five sessions per week for eight weeks, and the resistance training group performed three sessions per week with increasing load. 48 hours after the last training session, the animals in the experimental groups were anesthetized with ketamine and xylazine, blood samples were taken from the inferior vein, and quadriceps muscle tissue was quickly removed. CXCL1 gene expression level in quadriceps muscle and liver enzymes were measured as an indicator of liver function in serum. Statistical data were analyzed using one-way analysis of variance (P < 0.05).Results: The results of this research showed that after 8-weeks of interval and resistance training with increasing load, the expression level of the CXCL1 gene was higher in the quadriceps muscle of the control group, but no significant difference was found. The level of liver enzymes was significantly higher than the control group. The results also showed that spirulina consumption combined with interval aerobic and resistance exercise can significantly alter liver function indicators compared to the control group. However, the expression of the CXCL1 gene in the groups consuming spirulina and aerobic and resistance training did not show a significant change compared to the control group.Conclusion: the results of this research showed that spirulina and interval and resistance exercises can modulate the functional indicators of the liver and the gene expression of CXCL1 in the quadriceps muscle tissue. These results show that spirulina can be involved in the occurrence of adaptive responses related to metabolic damage.